영어 학습에서의 AI 활용에 대한 고등학생의 인식 연구 - 김진선; 맹은경 (영어교과교육, 2024)
The purpose of this study is to explore high school students’ perceptions of using AI tools in learning English and to investigate how gender impacts these perceptions. A total of 194 students from a high school in Gyeonggi Province participated in the survey. Data were analyzed using mean, percentage, standard deviation, independent sample t-tests, and repeated measures ANOVA. Open-ended responses were categorized, and a thematic frequency analysis was also conducted. The findings are summarized as follows: 1) Students showed a positive perception of AI tools’ convenience and a willingness to use them. 2) Perceptions of the educational effectiveness and interest and satisfaction were also high, though slightly lower. Frequency analysis supports these results, revealing positive views on AI tools’ usefulness, but some concerns about learning effectiveness and information reliability. Most students viewed AI tools’ convenience positively, with minimal negative feedback. 3) A significant gender-based difference was observed only in the perception of interest. The study also discusses the implications and suggestions arising from these findings.
Keywords: AI tools/perceptions; convenience to use; educational effectiveness; satisfaction; AI; 도구; 인식; 활용의 편리성; 교육적 효능성; 만족도